THE INFLUENCE OF STORE ATMOSPHERE ON CONSUMER PURCHASING DECISIONS AT THE EIGER STORE: (Study on the Eiger Store at Setia Budi Street, Medan) - Iqbal, Khairul; Siregar, Onan Marakali (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study seeks to explore how Store Atmosphere influences consumer purchase decisions on Eiger Store Setia Budi, Medan. This study's population consisted of customers of the Eiger Store Setiabudi Medan. The samples taken were 96 respondents. The data was obtained by distributing the questionnaires. Data analysis was done by Simple linear analysis and instrument tests in the form of validity, reliability, and classical assumption tests in the form of normality and heteroscedasticity tests, as well as hypothesis testing utilizing the T test and coefficient of determination test. According to the findings of this study, the Store Atmosphere has a positive and significant influence on purchasing decisions. This is evident from the 0,540 value of the regression coefficient for the variable Store Atmosphere (X). The t value of the Store Atmosphere (X) variable was 6,299 with a significance level of 0,000, as determined by researchers using a partial test (T-Test) to test the null hypothesis. The value of t table (df = 96 - 2) is 1,985, therefore t statistic > t table (6,299 > 1,985) and it can be concluded that the Store Atmosphere variable has a significant influence on purchase decisions, as indicated by the significant value 0,000 < 0,050.